(untitled) (Sport - nauka i praksa, 2023)
The main aim of this transversal study was to examine the relevant differences between the constructs of quality of life and exercise motivation among male and female adolescents of average and increased body mass. The sample included high school students from Valjevo (N = 337). The average age of the participants was M = 16.53 years (SD = .38). Two measuring instruments were used: The Exercise Motivations Inventory-2 (EMI-2) and The Kidscreen Questionnaire -27 (TKQ). The results of the Cronbach’s alpha suggested that the questionnaires used in the research have satisfactory level of reliability and internal consistency, and are valid for assessing adolescent population in Serbia. The research has shown that there are internal and external motives for adolescents’ exercise motivation, and that the male adolescents more favourably perceive the quality of life. Statistically significant gender differences were found, there was higher level of the evaluation of the TKQ construct among male adolescents than female adolescents which is the consequence of a more substantial view of physical well-being, pleasant feelings and moods, good family and social environment, as well as the ability to organize and arrange free time. It was also found that participants with average body mass prefer the perception of own physical activity and health more than their peers with increased body mass. Male adolescents do physical exercise for enjoyment, challenge, competition, strength and endurance, as well as for social reasons (factors such as belonging to a group, pressure, and acceptance), whereas female participants are more willing to exercise in order to control their body mass. The results of the Mann–Whitney U test revealed relevant gender differences: adolescents with average body mass are more likely to exercise because they enjoy the activity, while adolescents with increased body mass are more stimulated by the possibility of body mass regulation (p ≤ .01). This research discussed practical implications of the results on creating the motivation for exercise and quality of life among adolescents of both sexes with normal and increased body mass (BM).